Growth in spending on substance use disorder treatment services for the privately insured population. (1st March 2016) - Thomas, Cindy Parks; Hodgkin, Dominic; Levit, Katharine; Mark, Tami L.
Highlights: Private spending on substance use disorder (SUD) treatment accelerated after 2009. Two-thirds of the growth was driven by outpatient use and price increases. Despite high growth, SUD treatment rates remained low. Young adult SUD treatment use increased 41% after Affordable Care Act implementation. Increased SUD use by young adults had little effect on overall health spending. Abstract: Background: Approximately 8% of individuals with private health insurance in the United States have substance use disorders (SUDs), but in 2009 only 0.4% of all private insurance spending was on SUDs. The objective of this study was to determine if changes that occurred between 2009 and 2012 – such as more generous SUD benefits, an epidemic of opioid use disorders, and slow recovery from a recession – were associated with greater use of SUD treatment. Methods: Data were from the 2004–2012 Truven Health Analytics MarketScan ® Commercial Claims and Encounters Database. This database is representative of individuals with private insurance in the United States. Per enrollee use of and spending on SUD treatment was determined and compared with spending on all health care services. Trends were examined for inpatient care, outpatient care, and prescription medications. Results: During the 2009–2012 time period, use of and spending on SUD services increased compared with all diagnoses. Two-thirds of the increase was driven by higher growth rates in outpatient use and prices. Despite the high growth rates, SUD treatment penetration rates remained low. As of 2012, only 0.6% of individuals with private insurance used SUD outpatient services, 0.2% filled SUD medication prescriptions, and 0.1% used inpatient SUD services. In 2012, SUD services accounted for less than 0.7% of all private insurance spending . Conclusions: Despite recent coverage improvements, individuals with private health insurance still may not receive adequate levels of treatment for SUDs, as evidenced by the small proportion of individuals who access treatment.